Judicial Consistency dalam Putusan Mahkamah Konstitusi tentang Pengujian Undang-Undang Penodaan Agama - Zaka Firma Aditya (Jurnal Konstitusi, 2020)
This paper will discuss the consistency of the constitutional court decision in the judicial review cases based on the principle of precedent. MK several times deemed inconsistent because often issued a ruling that is overruling. However, there were actually a lot of MK decisions that consistently followed the precedent. Although the use of the precedent principle is only known in common law tradition, the Constitutional Court apparently also applies it. The Constitutional Court’s decision regarding the Blasphemy Prevention Act was one form of the principle of precedent in the Constitutional Court. This decision consistently states that the Blasphemy Prevention Act remains constitutional because a legal vacuum will occur if the Blasphemy Prevention Law was decided to be unconstitutional. In this case, the Court retained its ratio decidendi to the constitutionality of the Blasphemy Prevention Law, even though the Court was aware that the Law contained many weaknesses. The consistency of the Constitutional Court on the judicial review of the Blasphemy Prevention Act is one form of the practice of precedent doctrine.